Mesenchymal stem cell-derived extracellular vesicles therapy for primary ovarian insufficiency: a systematic review and meta-analysis of pre-clinical studies - Shahryar Rajai Firouzabadi; Ida Mohammadi; Kiana Ghafourian; Seyed Ali Mofidi; Shahrzad Rajaei Firouzabadi; Seyed Mahmoud Hashemi; Fahimeh Ramezani Tehrani; Kyana Jafarabady (BMC, 2024)
Abstract Background Primary ovarian insufficiency (POI) manifests with hormonal imbalances, menstrual irregularities, follicle loss, and infertility. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) are emerging as a promising treatment for POI. This systematic review aims to assess the effects of MSC-EVs on follicle number, hormonal profile, and fertility in POI animal models. Methods A systematic search of PubMed, Scopus, and Web of Science databases up to December 14th, 2023 was conducted. Two reviewers independently conducted screening, risk of bias assessment, and data extraction. Meta-analysis was performed to analyze treatment versus control outcomes using a random effects model. Publication bias was assessed using Egger's regression test and sensitivity analysis was assessed using the leave-one-out method. Subgroup analyses and meta-regressions were conducted based on EV source, induction model, type of animal, study quality, administration route, administration frequency and route, and dose. Results a total of 29 studies were included. MSC-EVs treatment significantly increased total follicle count (SMD, (95CI), p-value; 3.56, (0.91, 6.21), < 0.001), including primordial (SMD, (95CI), p-value; 2.86, (1.60, 4.12), < 0.001), primary (SMD, (95CI), p-value; 3.17, (2.28, 4.06), < 0.001), mature (SMD, (95CI), p-value; 2.26, (1.02, 3.50), < 0.001), and antral follicles (SMD, (95CI), p-value; 2.44, (1.21, 3.67), < 0.001). Administration frequency and route did not affect this outcome, but EV source affected primordial, primary, secondary and antral follicle count. Additionally, MSC-EVs treatment elevated anti-müllerian hormone (SMD, (95CI); 3.36, (2.14, 4.58)) and estradiol (SMD, (95CI); 3.19, (2.20, 4.17)) levels while reducing follicle stimulating hormone levels (SMD, (95CI); -2.68, (-4.42, -0.94)). Unlike EV source, which had a significant impact on all three hormones, administration frequency, route, and EV dose did not affect this outcome. Moreover, treatment increased offspring number (SMD, (95CI); 3.70, (2.17, 5.23)) and pregnancy odds (OR, (95CI); 10.25, (4.29, 24.46)) compared to controls. Publication bias and a high level of heterogeneity was evident in all analyses, except for the analysis of the pregnancy odds. However, sensitivity analysis indicated that all of the analyses were stable. Conclusion MSC-EVs therapy shows promise for POI treatment, potentially facilitating clinical translation. However, Further research is warranted to optimize methodology and assess side effects.